DEFECT FORMATION IN POLYCRYSTALLINE α-Al2O3 UNDER EXPOSURE TO NEUTRAL AND CHARGED PARTICLE BEAMS (American Journal of Technology and Applied Sciences, 2026)
In this work, point and low-dimensional defects formed in the near-surface layer of single-crystal α-Al2O3 under the influence of high doses of 4 MeV electron irradiation were investigated. The experiments were carried out on the Elektronika U-003 accelerator in the dose range of 1014–1017 cm-2 with current pulses of 4.5∙10-6 s duration and a beam density from 0.4 to 3 μA/cm2. Using scanning electron microscopy with local elemental analysis, the formation of stable fluorine and magnesium impurities in the irradiation region was established, which indicates radiation-stimulated transmutation processes in the crystal lattice of aluminum oxide. The obtained data are important for understanding the radiation resistance of aluminum oxide-based ceramics under extreme conditions, for example, as structural and insulating materials in nuclear power engineering and space technology.